Селекція троянд: історія, досягнення, сучасна стратегія - Rubtsova, O.L.; Chizhankova, B.I.; Boyko, R.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2015)
Results of the conducted research have shown that morphological features of roses (quantity of petals, shape and colour of a flower, quantity of flowers per inflorescence, inflorescence form and plant’s mien) and flowering period have changed significantly because of long-term cultivation and breeding. Further rose breeding activity should be aimed at improving biological features: winter, drought, diseases and pest resistance. With this aim, it is necessary to expand the use of genetic resources provided by wild species, which are one of the most important components of biodiversity